(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Philosophical analysis of the basic concepts of the information society involves the disclosure of its essence, understanding the roles and meanings of general information flows, in which a person is included as a part of nature and an element of the universe, determines promising directions. Moreover, each concept has its own approach to the study of the information society and, ultimately, considers its individual aspects using its own research methods.